2020
DOI: 10.5897/ajpp2020.5146
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of Camellia sinensis plant extracts against uropathogenic E. coli in vitro and in vivo

Abstract: This study evaluated the in vitro and in vivo antibacterial activities of methanol and ethyl acetate extracts of Camellia sinensis (Green tea) against Escherichia coli implicated in urinary tract infections. Antibacterial activities of these plant extracts were tested against 10 multi-drug resistant E. coli isolates obtained from clinical specimens of UTI patients. Forty-five (45) Wister albino rats were used for this study and exactly 0.1 ml of standardized (0.5 McFarland's) E. coli suspension was each inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Rekha et al also revealed the antibacterial action of Azadirachta indica , Centella asiatica , and C. ternatea extracts and their minimum inhibitory concentration against pathogens like S. aureus , P. aeruginosa , and Klebsiella sp., showing significant pathogen inhibition [ 19 ]. A study by Agbom et al related to C. sinensis extracts found that the methanol extract was more effective than the ethyl acetate extract in restoring health markers in infected rats, suggesting green tea’s potential in treating bacterial infections [ 11 ]. Kaewkod et al also discovered that green, oolong, and black tea, along with Thai medicinal plants, especially green tea, and Garcinia cowa , inhibit enteric bacteria due to their phenolic and flavonoid content [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rekha et al also revealed the antibacterial action of Azadirachta indica , Centella asiatica , and C. ternatea extracts and their minimum inhibitory concentration against pathogens like S. aureus , P. aeruginosa , and Klebsiella sp., showing significant pathogen inhibition [ 19 ]. A study by Agbom et al related to C. sinensis extracts found that the methanol extract was more effective than the ethyl acetate extract in restoring health markers in infected rats, suggesting green tea’s potential in treating bacterial infections [ 11 ]. Kaewkod et al also discovered that green, oolong, and black tea, along with Thai medicinal plants, especially green tea, and Garcinia cowa , inhibit enteric bacteria due to their phenolic and flavonoid content [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a high concentration of polyphenols, such as flavonoids and catechins, which support its anti-inflammatory and anticancer activities [ 10 ]. Agbom et al’s study shows that C. sinensis (green tea) methanol and ethyl acetate extracts have bioactive ingredients, and the methanol extract exhibited higher antibacterial activity against the test uropathogenic E. coli isolates at lower concentrations than ethyl acetate extract [ 11 ]. Likewise, Sharma and Pundir’s study shows that the leaves of C. sinensis exhibit antibacterial and antifungal properties, making them a potential alternative to current therapeutic agents with fewer side effects on human skin [ 12 ].…”
Section: Introductionmentioning
confidence: 99%